A Strategic Social Action Framework: Theorizing and analyzing the alignment of social media affordances and organizational social action. Issue 2 (3rd April 2017) - Van Osch, Wietske; Coursaris, Constantinos K.
ABSTRACT: Social media is a relatively new and dynamic field dealing with the development and use of social media technologies by individuals and more recently by organizations. Although several frameworks and models have been proposed for studying social media, most provide only limited insights into the complex social activities that are supported by the strategic usage of social media in organizational settings. In this article, we take up this challenge and introduce a Strategic Social Action Framework for analyzing social media technologies and their strategic usage in and by organizations. This framework is based on Habermas' theory of social action and the idea that social media platforms serve as sets of rules and resources that mediate strategic organizational (inter-)actions involving these platforms. We demonstrate the value of the framework by theoretically delineating the appropriateness of the framework to specific social media tools, as well as by empirically analyzing the strategic use of two publicly available social media platforms—Facebook and Twitter—by three large airlines—Delta, KLM Royal Dutch Airlines, and JetBlue. Our findings reveal that when implementing social media in organizational contexts, developers and managers should critically evaluate (a) the need for supporting a rich variety of action types, (b) the possible role of social media support in the specific action situation, and (c) the strategic alignment of social media affordances and specific social action categories. Finally, we discuss theoretical and practical implications as well as directions for future research.